Promoting Newsafety from the Exile: The Emergence of New Journalistic Roles in Diaspora Journalists' Networks. (21st October 2022) - Porlezza, Colin; Arafat, Rana
ABSTRACT: Diaspora journalists and digital media play an important role as stakeholders for war-ridden homeland media landscapes such as Syria. This study analyzes, from a safety in practice perspective, the physical and digital threats that challenge the work of Syrian citizen journalists examining the role of three online advocacy networks created by Syrian diaspora journalists to promote newsafety. Through a metajournalistic discourse analysis of the networks' published visions and missions, and 12 in-depth interviews with the founders and other selected members of the networks, the paper investigates how journalists working for these networks perceive threats, what counterstrategies they adopt, and how they understand the changing nature of their roles. Findings demonstrate that diaspora journalists perceived physical and digital threats as inescapable, following them across borders. Counterstrategies are implemented through collaborations with civil society actors and human rights organizations, aiming to offer professional safety training programs and emergency rescue for journalists under attack, but also through the release of safety guides or codes of conduct. Grounded on the findings, we propose four novel journalistic roles for promoting newsafety from exile: sousveillance, defender, trainer, and regulator/policy developer. While the networks follow some traditional journalistic ideologies, they also show a hybrid conceptualization of journalism.